Nitrogen Mineralization from Anaerobically Digested Centrifuge Cake and Aged Air‐Dried Biosolids. (1st September 2014) - Kumar, Kuldip; Hundal, Lakhwinder S.; Cox, Albert E.; Granato, Thomas
ABSTRACT: : This study was conducted to estimate nitrogen (N) mineralization of anaerobically digested centrifuge cake from the Stickney Water Reclamation Plant (SWRP) and Calumet Water Reclamation Plant (CWRP), lagoon‐aged air‐dried biosolids from the CWRP, and Milorganite at three rates of application (0, 12.5 and 25 Mg ha −1 ). The N mineralized varied among biosolids as follows: Milorganite (44%) > SWRP centrifuge cake (35%) > CWRP centrifuge cake (31%) > aged air‐dried (13%). The N mineralized in the SWRP cake (32%) and CWRP aged air‐dried biosolids (12%) determined from the 15 N study were in agreement with the first study. The N mineralization value for centrifuge cake biosolids observed in our study is higher than the value given in the Part 503 rule and Illinois Part 391 guidelines. These results will be used to fine‐tune biosolids application rate to match crop N demand without compromising yield while minimizing any adverse effect on the environment.